Toward the Charter : Canadians and the demand for a national bill of rights, 1929-1960 - Maclennan, Christopher, 1968- (McGill-Queen's University Press, 2003)
"Toward the Charter looks at the evolution of human rights in Canada through Canadian efforts to entrench a bill of rights in the constitution. The important roles played by parliamentarians such as John Diefenbaker and academics such as F.R. Scott are placed alongside those of trade unionists, women, and a long list of individuals representing Canada's multicultural groups to reveal the diversity of the bill of rights movement. At the same time MacLennan weaves Canadian-made arguments for a bill of rights with ideas from the international human rights movement led by the United Nations to show that the Canadian experience can only be understood within a wider, global context."--Jacket